Activation of human telomerase reverse transcriptase through gene fusion in clear cell sarcoma of the kidney. Issue 2 (28th February 2015) - Karlsson, Jenny; Lilljebjörn, Henrik; Holmquist Mengelbier, Linda; Valind, Anders; Rissler, Marianne; Øra, Ingrid; Fioretos, Thoas; Gisselsson, David
Highlights: The first report on RNA-sequencing data of clear cell sarcoma of the kidney (CCSK). A novel fusion, IRX2-TERT, was identified that lead to increased TERT expression. Telomerase reverse transcriptase can be activated via fusion transcripts. A previously published YWHAE-NUTM2B/NUTM2E fusion was found in 2/22 CCSKs. The majority of CCSKs appear to lack fusion transcripts. Abstract: Clear cell sarcoma of the kidney (CCSK) is a rare tumor type affecting infants and young children. Most CCSKs display few genomic aberrations, and no general underlying mechanism for tumor initiation has yet been identified, although a YWHAE-NUTM2B/NUTM2E fusion gene has been observed in a minority of cases. We performed RNA-sequencing of 22 CCSKs to investigate the presence of additional fusion transcripts. The presence of the YWHAE-NUTM2B/NUTM2E fusion was confirmed in two cases . In addition, a novel IRX2-TERT fusion transcript was identified in one case. SNP-array analyses revealed the underlying event to be an interstitial deletion in the short arm of chromosome 5 (5p15.33). TERT was dramatically upregulated under the influence of the IRX2 promoter. In line with TERT expression being driven by active IRX2 regulatory elements, we found a high expression of IRX2 in CCSKs irrespective of fusion gene status. IRX2 was also expressed in human fetal kidney – the presumed tissue of origin for CCSK. We conclude that in addition to promoter mutations and epigenetic events, TERT can also be activated in tumors via formation of fusion transcripts.